Application of Story Maps Techniques in Visualizing the Tourism Potential of Lake Toba in North Sumatera Province - Matondang, Farouq (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2021)
Lake Toba is a lake located in the caldera of Mount Supervolcano. Lake Toba is also the largest lake in Southeast Asia. Lake Toba is included in the National Tourism Strategic Area (KSPN). This study aims to present information that is more interactive and communicative so that it is moreinteresting and easy to understand. This study aims to (1) visualize the potential of tourism objects in Lake Toba (2) Increase tourism promotion in North Sumatra, especially Lake Toba through the Story Maps technique. The research method used is descriptive. The results of this study are interactive maps of web-based tourist objects using Story Maps.